Recognising Faces: Effects of Lighting Direction, Inversion, and Brightness Reversal. (November 2013) - Johnston, Alan; Hill, Harold; Carman, Nicole
When information about three-dimensional shape obtained from shading and shadows is ambiguous, the visual system favours an interpretation of surface geometry which is consistent with illumination from above. If pictures of top-lit faces are rotated the resulting stimulus is both figurally inverted and illuminated from below. In this study the question of whether the effects of figural inversion and lighting orientation on face recognition are independent or interactive is addressed. Although there was a clear inversion effect for faces illuminated from the front and above, the inversion effect was found to be reduced or eliminated for faces illuminated from below. A strong inversion effect for photographic negatives was also found but in this case the effect was not dependent on the direction of illumination. These findings are interpreted as evidence to suggest that lighting faces from below disrupts the formation of surface-based representations of facial shape.